2011
DOI: 10.1007/s12633-011-9074-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Chain Relaxation Mechanisms in Siloxane-Carbosilane Systems

Abstract: The effect of sterically hindered carbosilane moieties, situated as end groups in telechelic oligodimethylsiloxanes, was investigated with respect to the mobility of silicon atoms in the main chain. The relaxation phenomena in such crowded systems were studied by DSC and NMR methods. Spin-lattice relaxation times T 1 ( 29 Si NMR) of silicon atoms in the oligomer chain were estimated and related to the distance between a given siloxane unit and the carbosilane moiety. It was found that the mobility of terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The bulky nature of the silane surface treating agent may also be partly responsible for this chain restriction and lowering of the elongation at break. Similar results are reported by other researchers 22,23 .…”
Section: Resultssupporting
confidence: 93%
“…The bulky nature of the silane surface treating agent may also be partly responsible for this chain restriction and lowering of the elongation at break. Similar results are reported by other researchers 22,23 .…”
Section: Resultssupporting
confidence: 93%
“…A slow decrease of sample weight at 500–700 °C indicates that the subsequent degradation process is not based on the depolymerization of polysiloxanes but involves a range of complex phenomena. We noted a similar increase in the thermal stability of linear polysiloxanes grafted with derivatives of sterically demanding tris(trimethylsilyl)methane, both as terminal [ 62 ] and side groups [ 58 ]. Thus, the increase in thermal stability of linear polysiloxanes grafted with eugenol and linalool may be related to a reduction in the extent of thermal depolymerization by chain scission.…”
Section: Resultsmentioning
confidence: 80%
“…The relaxation phenomena were studied by DSC and NMR methods with respect to the mobility of silicon atoms in the main chain. 33 The measured spin-lattice relaxation times T 1 ( 29 Si NMR) of silicon atoms in siloxane chain were related to the distance between a given siloxane unit and the carbosilane moiety. It was found that the mobility of terminal siloxane units was substantially hindered, but the short range effects did not outweigh the intrinsic exibility of siloxane bonds and the mobility of other silicon atoms was almost not affected.…”
Section: T Si -Substituents In Linear Siloxane Polymers and Oligomersmentioning
confidence: 99%
“…6). 33 The size of bulky end group [T Si (A) or T Si (B)] has no signicant inuence on the thermal stability of the oligo(dimethylsiloxanes). The steric hindrance provided by T Si groups works only for the siloxane units close to the immobilized chain end.…”
Section: Linear Polymersmentioning
confidence: 99%